2012
DOI: 10.14221/ajte.2012v37n7.3
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service Teachers’ Conceptions of Education for Sustainability

Abstract: Environmental education researchers argue that preservice teachers have a limited understanding of education for sustainability. The research described in this article applies a phenomenographic approach to investigating variations in how a representative cohort of 30 pre-service teachers, at various stages of completing an education degree at a small regional Australian university, understands the concept of education for sustainability. The results distinguish four related but distinctive categories of descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…In fact, for [63], 'teachers' (and pre-service teachers') pedagogical and environmental beliefs are more important in guiding their teaching about controversial socio-ecological issues than have previously been recognised' (p. 69). Then, if we accept that what teachers know and believe directly affects classroom content regarding EDS [64], and because of the lack of insights into these issues [63,65], more research is needed to go further into the difficulties that pre-service teachers find when they build the relationship between sustainability and their lifestyle.…”
Section: Conservation Of Socio-ecological Systems Based On Our Everydmentioning
confidence: 99%
“…In fact, for [63], 'teachers' (and pre-service teachers') pedagogical and environmental beliefs are more important in guiding their teaching about controversial socio-ecological issues than have previously been recognised' (p. 69). Then, if we accept that what teachers know and believe directly affects classroom content regarding EDS [64], and because of the lack of insights into these issues [63,65], more research is needed to go further into the difficulties that pre-service teachers find when they build the relationship between sustainability and their lifestyle.…”
Section: Conservation Of Socio-ecological Systems Based On Our Everydmentioning
confidence: 99%
“…Whole-school approaches have been consistently shown to support successful EEfS implementation (Lewis, Baudains, & Mansfield, 2009; Shallcross & Robinson, 2008). Active support from principals has been shown to encourage primary teachers, enabling them to overcome some of the initial hesitancies in implementing EEfS (Evans, Whitehouse, & Hickey, 2012). A study conducted in New South Wales and Victoria (Flowers & Chodkiewicz, 2009) reinforced the credibility of whole-school approaches.…”
Section: Findings: Core Issues and Themesmentioning
confidence: 99%
“…The studies conducted on teachers and pre-service teachers' attitudes towards and beliefs about education for sustainability in recent years focus on the place of the discourse of social gender equality within the framework of the targets of sustainable development (Sharma, 2016), whether pre-service teacher training programs can be a tool for making sustainability more widespread (Ferreira et al, 2009); the effect of pre-service teachers' self-reported ESD on self-efficacy and their attitudes towards ESD (Evans, Tomas, & Woods, 2016); variables affecting how pre-service teachers understand the concept of education for sustainability (Evans et al, 2012); development of sustainability kit (Gardner, 2017). Ajzen (2002, p. 5) defines attitudes towards behavior as "a person's general positive or negative evaluations related to exhibition of the behavior".…”
Section: Introductionmentioning
confidence: 99%